2020
DOI: 10.1111/medu.14151
|View full text |Cite
|
Sign up to set email alerts
|

Today's doctors: What do men and women value in a training post?

Abstract: Objectives: Recent studies suggest that traditional male-female differences may be changing in terms of what is valued in a medical career but there have been no studies directly quantifying the relationship between gender and stated career-related preferences. To address this gap, we examined the differences between male and female doctors in terms of the strength of their work-related preferences at the point of eligibility to enter residency or specialty training in the UK. Methods:This was a quantitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…As several studies have shown that factors such as income, prestige, and procedural activities are more important to male physicians, results of this study may indicate that the pattern of choosing a specialty among women is changing. These findings are consistent with a study by Scanlan et al which showed that gender norms of career selection are changing [ 66 ]. National policies could be developed to address undesirable gender trends in the selection of specialty courses.…”
Section: Discussionsupporting
confidence: 93%
“…As several studies have shown that factors such as income, prestige, and procedural activities are more important to male physicians, results of this study may indicate that the pattern of choosing a specialty among women is changing. These findings are consistent with a study by Scanlan et al which showed that gender norms of career selection are changing [ 66 ]. National policies could be developed to address undesirable gender trends in the selection of specialty courses.…”
Section: Discussionsupporting
confidence: 93%
“…among foundation doctors in the UK suggested that the traditional gender gap in specialty selection may be narrowing. [ 44 ] Furthermore, Baschera women et al . discussed that gender might not be a significant determinant of preference for non-surgical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…These were the lack of mentor and female models which would make it possible to create vocations, difficulties in time management linked to clinical, research, and teaching activities together, which characterizes the French university hospital model, and a lower interest in research on women's part. As Scanlan et al pointed out, many studies have been done on a single specialty or on small numbers of students, but few on a group of students from several specialties [9].…”
Section: Introductionmentioning
confidence: 99%